The Actual Problems of Modern Linguistics (Texas Journal of Philology, Culture and History, 2023)
This article describes thoroughly the actual problems of linguistics, the utmost possible study of linguistic and speech phenomena, the relationship of linguistics with various disciplines, the priorities of the organization of higher education